SOCIAL STATUS OF SCIENTIFIC ACTIVITY IN THE MINDS OF THE YOUTH OF KAZAKHSTANI - Lepeshev, Dmitry Vladimirovich; Teslenko, Alexander Nikolaevich (European Scientific Journal, ESJ, 2014)
This article considers the social status of science and education, and the factors of its formation in cases of higher school in the Republic of Kazakhstan. For a better understanding of social status and image of science in the consciousness of young people, a sociological survey was conducted among pupils and students of the Republic of Kazakhstan. In addition, the article discusses the problem in attracting young people to science and their solutions.